Evaluation of Crop Water Status and Vegetation Dynamics For Alternate Partial Root-Zone Drip Irrigation of Alfalfa: Observation With an UAV Thermal Infrared Imagery - Lu, Saihong; Zhang, Tong; Tian, Fei (Frontiers in Environmental Science, 2022)
Characterization of the spatial and temporal patterns of crop water status and vegetation dynamics are a prerequisite to overcome water scarcity and obtain precise agricultural water management. Based on high-resolution aerial thermal images and field study, we estimated the following for alfalfa: its spatiotemporal patterns crop water stress index (CWSI), transpiration rate (T), and crop growth status variability. The research was conducted on alfalfa with traditional drip irrigation (abbreviated as R) and with alternate partial root-zone drip irrigation (abbreviated as P) under four different irrigation treatments: 0 mm, 10 mm, 20 mm, and 30 mm irrigation quotas in both nutritional growth and reproductive growth periods, which are denoted as CK (no irrigation), R10 (P10), R20 (P20), and R30 (P30), respectively. Results indicate that the CWSI is a suitable tool to define alfalfa water status variability and assess the spatiotemporal dynamics under different irrigation regimes. Under the same irrigation method, the CWSI values reflect CK>R10>R20>P10>P20>R30>P30 during the growing season, with values of 0.57, 0.41, 0.26, 0.24, 0.18, 0.17, and 0.13, respectively. Meanwhile, the T values show that CK